New Derivatives of (E)-3-(5-((substitutedphenylamino)methyl)-1,3,4-thiadiazol-2-yl)-2-styryl quinazolin-4(3H)-one: Searching for New Antifungal and Antibacterial Agents: New Derivatives of (E)-3-(5-((substitutedphenylamino)methyl)-1,3,4-thiadiazol-2-yl)-2-styryl quinazolin-4(3H)-one: Searching for New Antifungal and Antibacterial Agents - Sahu, Aditya (International Journal of Pharmaceutical & Biological Archive, 2020)
Objective: The objective of the paper was to evaluate the antifungal and antibacterial potential of new derivatives of ((E)-3-(5-((substitutedphenylamino)methyl)-1,3,4-thiadiazol-2-yl)-2-styryl quinazolin-4(3H)-one. Materials and Methods: Various syntheses of (E)-3-(5-(substitutedaminomethyl)-1,3,4-thiadiazol-2-yl)-2-styrylquinazolin-4(3H)-one derivatives have been synthesized by reacting 2-substituted benzoxazin-4-one with (E)-2-(4-Substituedstyryl)-4H-benzo[d] [1,3]oxazin-4-one. All synthesized compounds have been characterized by the infrared, 1HNMR, and mass spectral analysis. Proposed compounds have been evaluated for antifungal and antibacterial activity. The antimicrobial activity of synthesized compounds (QNM-1 to QNM-15) has been carried through the serial dilution method. For bacterial screening, bacterial species were taken includes Staphylococcus aureus (MTCC-96), Bacillus subtilis (MTCC-441), Pseudomonas aeruginosa (MTCC-424), and Escherichia coli (MTCC-40). Norfloxacin (1-Ethyl-6-fluoro-1,4,dihydro-4-oxo-7-(1-piperazinyl)-3-quinoline carboxylic acid) was used as the standard drug for antibacterial study. For antifungal screening, the following fungal species were used includes Aspergillus niger (MTCC-281), Candida albicans (MTCC-227), and Fusarium oxysporum (MTCC-284). Clotrimazole was selected as a standard drug for antifungal study. Results and Discussion: QNM-1, QNM-2, QNM-3, QNM-5, QNM-7, QNM-9, QNM-12, QNM-14, and QNM-15 were the most active compounds [Table 1] in the synthesized series which were active against both Gram-positive and Gram-negative organisms by the antibacterial screening. In the case of antibacterial activity, the presence of electronegative group (Cl, Br, F, and NO2) at both R may enhance the activity when they are p-substituted, but the compounds QNM-6 (R1=-C6H5Br (o); Ar=-C6H5), QNM-10 (R1 = -C6H5F (o); Ar= -C6H5F), QNM-11 (R1 =-C6H5NO2 (p); Ar=-C6H5F), and QNM-4 (R1 =-C6H5F (m); Ar=-C6H5) with given substitution may result in diminishing the activity. In case of antifungal activity, compounds QNM-1, QNM-5, QNM-7, QNM-9, QNM-11, QNM-12, QNM-14, and QNM-15 were the most active compounds in the synthesized series which were active against both Gram-positive and Gram-negative organisms. In that series, compounds QNM-14, QNM-11, QNM-5, and QNM-7 have shown the highest activity. Compounds QNM-3, QNM-6, QNM-10, and QNM-13 have the least active. This result has also concluded that o-substituted compounds, i.e., -C6H5Cl(o), -C6H5Cl (m), -C6H5Br(o), -C6H5F (o), -C6H5F (p) at R1 position my resulted in diminishing or lower the activity.